2009
DOI: 10.1002/adma.200900582
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured Surfaces Cause Severe but Non‐Detrimental Deformation of the Cell Nucleus

Abstract: Surface features on the length scale of organelles allow their manipulation. Here, we present observations of an unexpected deformation of nuclei within cells growing on surfaces with micrometer‐sized pillars. Our results demonstrate that a microstructured surface can induce strong shape deformations in cells, without harmful consequences, and strongly suggest that these are limited to cancerous cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
122
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 17 publications
7
122
1
Order By: Relevance
“…These results suggest that the most promising dimensions for creating such an environment for D1 cells are gap widths of $15 lm, which would result in a majority of cells located between posts, and post sizes of at least 5 lm. Deformation of the cell body to squeeze into gaps has been previously demonstrated on a rigid, non-porous substrate [42], but cells on polyacrylamide benefit from access to nutrients in three dimensions, due to the hydrogel porosity, and are in an environment with tissue-like elasticity. Several researchers have used flat substrates of this hydrogel to demonstrate the influence of substrate elasticity on cell behavior [35,[43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that the most promising dimensions for creating such an environment for D1 cells are gap widths of $15 lm, which would result in a majority of cells located between posts, and post sizes of at least 5 lm. Deformation of the cell body to squeeze into gaps has been previously demonstrated on a rigid, non-porous substrate [42], but cells on polyacrylamide benefit from access to nutrients in three dimensions, due to the hydrogel porosity, and are in an environment with tissue-like elasticity. Several researchers have used flat substrates of this hydrogel to demonstrate the influence of substrate elasticity on cell behavior [35,[43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…At the cellebiomaterial interface, the interactions are mainly influenced by the surface characteristics of the biomaterial, including chemistry and topography [2,3,30,44]. In particular, topographical patterning has been shown to affect the behavior of cells, including triggering changes in cell shape and the subsequently induced alterations in the function and viability of the cells [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of adherent leukocytes was found to be dependent on surface topography, pattern geometry and surface chemistry of the substrate [18]. Davidson et al showed that interaction of the normal cells with the topographically patterned surfaces was different from that of the cancer cells and plasma membranes of the normal cells were not easily deformed when the contact area between surface and cells was increased [4]. Yan et al suggested that cell binding locations and properties can be controlled by designing specific micropattern sizes [29].…”
Section: Introductionmentioning
confidence: 99%
“…These interactions were related to five parameters such as type and percent distribution of the chemical groups on the surface [1], surface roughness [1][2][3][4][5], surface wettability [6][7][8], surface free energy (SFE) of the substrate [6,9], and size and shape of the cell used for testing [10,11]. The distance between surface patterns and focal adhesion clusters on the cell membrane is also an important parameter for the cell to form a strong adhesion on a substrate [1][2][3]12,13].…”
Section: Introductionmentioning
confidence: 99%